Market-oriented land transfers in rural Vietnam: navigating challenges for sustainable and equitable development - Trang Nguyen, Ngoc Minh; Cai, Zikun; Zhang, Tiantian (Frontiers in Environmental Science, 2025)
Market-oriented transfers of collectively owned rural land in Vietnam are pivotal for advancing rural development, enhancing agricultural productivity, and fostering socioeconomic progress. This study examines the challenges and opportunities associated with these transfers within Vietnam’s unique socio-political context. Despite significant changes since the implementation of the Đổi Mới economic policies in 1986, Vietnam continues to face obstacles such as land tenure insecurity, corruption in land administration, and socioeconomic disparities that limit access to land markets for lower-income farmers. Using a mixed-methods approach, the research integrates quantitative data from land transfer records and economic statistics with qualitative insights from interviews and focus group discussions conducted in the Red River Delta, Mekong Delta, and Central Highlands. Econometric models assess the impacts of land market activities on various economic indicators, while thematic analysis explores governance issues, tenure rights, and the socioeconomic consequences of land use. Econometric analysis revealed that land market activities significantly improved agricultural productivity, increased rural incomes, and stimulated investment, although risks of land concentration and rising rural inequalities persist. Findings indicate that while market-oriented land transfers can enhance agricultural production and stimulate rural investment, issues of land concentration and the potential exacerbation of rural inequalities persist. Environmental concerns, such as the risk of land over-exploitation leading to degradation, are also significant. These results underscore the imperative for Vietnam to implement reforms within its specific context. Comparative experiences from countries like China and Rwanda highlight that land fragmentation and social imbalance can emerge as detrimental consequences if not properly managed. Policy recommendations emphasize strengthening property rights, combating corruption through increased transparency and institutional safeguards, ensuring equitable access to land markets for smallholder farmers, and promoting sustainable land resource utilization. Enhancing institutional capacity and engaging international stakeholders are identified as crucial elements for effective policy implementation. In conclusion, careful and participatory policy formulation, along with effective execution, is essential for Vietnam to leverage the benefits of market-oriented land transfers while mitigating associated risks. Addressing the identified challenges can lead to a robust rural land system that supports agricultural productivity, promotes social equity, and protects the environment, ultimately contributing to the nation’s overall development. Future research should monitor the long-term impacts of these reforms on livelihoods, social dynamics, and the environment to inform ongoing policy refinement.